Robert N. Entman’s Framing Analysis of the Final Presidential Debate on Social Welfare in Cnnindonesia.com and Tempo.co (February 4-5, 2024) - Sitanggang, Natasya Ananda Rheta; Putri, Kinkin Yuliaty Subarsa; Romli, Nada Arina (Journal of Digital Marketing and Communication, 2025)
Indonesia, as a democratic country, routinely held presidential and regional elections every five years in accordance with Law Number 7 of 2017. The presidential candidate debate, as part of the election process and broadcast through various media, was one of the events the public eagerly anticipated. Media coverage, especially through online platforms such as Tempo.co and Cnnindonesia.com, played an important role in shaping public opinion through news framing. This study aimed to apply Robert N. Entman's framing analysis to compare how Tempo.co and Cnnindonesia.com framed the news of the final presidential debate on social welfare using qualitative descriptive methods. The findings of this study showed that the online media Cnnindonesia.com focused more on the details of specific programs and their substance, providing in-depth information that helped readers understand the free meal program comprehensively. In contrast, Tempo.co focused more on the verbal dynamics and interactions between candidates, with an emphasis on negative statements and responses. Thus, the construction of reality or framing carried out by the media impacted readers' perceptions of the presidential candidates through the debate program.